Dysregulation of macrophage development and phenotype in diabetic human macrophages can be rescued by Hoxa3 protein transduction. - Salma Alrdahe; Hadeel Al Sadoun; Tanja Torbica; Edward A McKenzie; Frank L Bowling; Andrew J M Boulton; Kimberly A Mace (PLoS ONE, 2019)
Controlled inflammatory responses of myeloid cells recruited to wounds are essential for effective repair. In diabetes, the inflammatory response is prolonged and augmented over time, with increased myeloid cells present in the wound that fail to switch from a pro-inflammatory phenotype to a pro-healing phenotype. These defects lead to delayed angiogenesis and tissue repair and regeneration, and contribute to chronic wound formation. In mouse models of diabetes, this aberrant phenotype is partially mediated by stable intrinsic changes to the developing myeloid cells in the bone marrow, affecting their maturation and polarization potential. Previous studies have shown that freshly isolated peripheral blood mononuclear cells from diabetic patients are more inflammatory than non-diabetic counterparts. However, the phenotype of macrophages from human diabetic patients has not been well characterized. Here we show that diabetic-derived human macrophages cultured for 6 days in vitro maintain a pro-inflammatory priming and hyperpolarize to a pro-inflammatory phenotype when stimulated with LPS and INF-ɣ or TNF. In addition, diabetic-derived macrophages show maturation defects associated with reduced expression of the RUNX1 transcription factor that promotes myeloid cell development. Targeting intrinsic defects in myeloid cells by protein transduction of the Hoxa3 transcription factor can rescue some inflammation and maturation defects in human macrophages from diabetic patients via upregulation of Runx1. In addition, Hoxa3 can modulate the levels of p65/NF-κB and histone acetyltransferase and deacetylase activity, as well as inhibit acetylation of the TNF promoter. Altogether, these results show a link between myeloid cell maturation and inflammatory responses, and that diabetes induces intrinsic changes to human myeloid cells that are maintained over time, as well as potentially therapeutic Hoxa3-mediated mechanisms of controlling the inflammatory response in diabetes.